Determination of in situ speciation of manganese in treated acid mine drainage water by using multiple diffusive gradients in thin films devices - de Oliveira, Rodrigo Lopes F. [UNESP]; Pedrobom, Jorge H. [UNESP]; Menegário, Amauri A. [UNESP]; Domingos, Roberto N. [UNESP]; Py, Delcy A.; Kiang, Chang Hung [UNESP] (Elsevier, 2013)
Acid mine drainage (AMD) is a serious environmental problem that creates acidic solution with high Mn concentrations. The speciation of residual Mn from AMD after an active treatment involving the addition of a neutralizing agent can reliably evaluate the treatment efficiency and provide knowledge of the Mn species being inputted into the environment. The aim of this study was to evaluate the in situ lability and speciation of Mn using the diffusive gradients in thin films (DGT) technique with treated drainage water from a uranium mine (TAMD). DGT devices with different binding phases (Chelex-100 and P81 and DE81membranes) were used to perform the in situ speciation of Mn. A comparison of the results from deploying DGT in the laboratory and in situ shows that the speciation of Mn in TAMD should be performed in situ. Linear deployment curves (from in situ experiments) indicate that the DGT device containing the Chelex-100 binding phase can be used to evaluate Mn lability in TAMD. The labile Mn fraction (from in situ measurements) obtained using the device containing the Chelex-100 resin ranged from 63 to 81% of the total Mn concentration and, when compared to the speciation obtained using the CHEAQS software, indicated that this device was capable of uptaking the free Mn2+ and a portion of the MnSO4(aq). The values obtained using the DGT technique were compared to those from on site solid phase extraction, and a good agreement was found between the results. The amount of negative Mn species sampled by DE81 device was insignificant (<1.5%) for all of the sites. Sites containing a relatively small amount of Ca (<40mgL-1) and measured using devices containing the P81 membrane agreed with the concentration predicted by the CHEAQS software for positive Mn species (Mn2+ and Mn(OH)+). Nevertheless, the speciation obtained using the CHEAQS software indicated that the concentrations of positive Mn species were underestimated for sites with relatively high Ca concentrations (>150mgL-1), which take place due to the saturation of binding sites in the P81 membrane. © 2013 Elsevier B.V.
Keywords: Acid mine drainage; Manganese; Passive sampler; Speciation; Uranium mine